Structural extracellular polymeric substances determine the difference in digestibility between waste activated sludge and aerobic granules. (15th August 2020) - Guo, Hongxiao; Felz, Simon; Lin, Yuemei; van Lier, Jules B.; de Kreuk, Merle
Abstract: Aerobic granular sludge (AGS) technology is an alternative to conventional activated sludge to reduce the process footprint and energy consumption. Strategies for the efficient management of its produced biomass, that is grown in a granular morphology as well, need further development. Anaerobic digestion (AD) is commonly applied in waste activated sludge (WAS) treatment and is a potential option also for produced AGS treatment. In earlier studies, the biochemical methane potential of AGS was found lower than that of WAS both grown in full-scale municipal wastewater treatment systems. In order to understand this difference, this study aimed to investigate the anaerobic conversion of structural extracellular polymeric substances (SEPS), which is a type of gel-forming biopolymer, being responsible for the aggregation of sludge. Using WAS and AGS as substrates, a comparative AD batch experiment was performed for 44 days during which the SEPS fraction was extracted from both types of sludge. The changes in the SEPS chemical composition was analysed by Fourier transformed infrared spectroscopy and three-dimensional excitation and emission matrix analysis. In addition, the mechanical strength of hydrogels of extracted polymers cross-linked with Ca 2+ ions was investigated by dynamic mechanical analysis. Results showed that the amount of SEPS was reduced by 26% in AGS (SEPSAGS ) and by 41% in WAS (SEPSWAS ), respectively. Polysaccharides and, to a lesser extent, the proteins in the SEPSAGS were more refractory compared to those in SEPSWAS . This resulted in a lower loss of the gel stiffness of SEPSAGS than that of SEPSWAS during the AD process. Moreover, the release of SEPS from tightly bound EPS to loosely bound EPS were observed in both types of sludge, but that in AGS exhibited a lower transition rate. The observed properties explain the distinct differences in anaerobic biodegradability, the slower decomposition of the sludge structure, as well as the better dewaterability of AGS as compared to WAS after the AD process. Graphical abstract: Image 1 Highlights: Anaerobic conversion of structural extracellular polymers (SEPS) was focused. SEPS was reduced more in waste activated sludge than aerobic granules. Polysaccharides and proteins in SEPS of aerobic granules were more refractory. SEPS from aerobic granules had lower loss of gel stiffness in anaerobic digestion. SEPS was released from tightly bound EPS to loosely bound EPS and slime.